Decarbonization and Improvement of Energy Efficiency of FSRU by Cryogenic CO2 Capture - Audrius Malūkas; Sergejus Lebedevas (Journal of Marine Science and Engineering)
Cryogenic Carbon Capture (CCC) has emerged as a promising technology to enhance the sustainability of Liquefied Natural Gas (LNG) operations in line with the International Maritime Organization’s (IMO) decarbonization targets. This study investigates the integration of CCC within Floating Storage and Regasification Units (FSRUs), leveraging LNG’s cryogenic potential to improve CO2 capture efficiency and optimize energy use. A detailed structural analysis of the FSRU’s energy balance was conducted considering variable regasification performance in open- and closed-loop regimes, followed by a Thermoflow-based simulation to assess the impact of CCC integration under real operational conditions. The results demonstrate that incorporating CCC into the FSRU’s closed-loop regasification process enables effective CO2 capture and separation from the flue gas emitted by the Wärtsilä 8L50DF and 6L50DF dual-fuel electric diesel generators, as well as the boiler system. The study identifies a potential fuel consumption optimisation of 22% and a CO2 capture rate of 100%, where the energy balance process requires 17.4 MW of combined energy unitisation. In addition, the study highlights the role of LNG cold energy potential in optimising heat exchange and mitigating thermal losses. These findings support the feasibility of CCC as a viable decarbonisation strategy for LNG FSRU operations. Future research should focus on improving system scalability and evaluating long-term performance under varying environmental and operational conditions.